Low‐frequency sounds induce acoustic trauma in cephalopods. Issue 9 (11th April 2011) - André, Michel; Solé, Marta; Lenoir, Marc; Durfort, Mercè; Quero, Carme; Mas, Alex; Lombarte, Antoni; van der Schaar, Mike; López-Bejar, Manel; Morell, Maria; Zaugg, Serge; Houégnigan, Ludwig
Abstract : There is currently relatively little information on how marine organisms process and analyze sound, making assessments about the impacts of artificial sound sources in the marine environment difficult. However, such assessments have become a priority because noise is now considered as a source of pollution that increasingly affects the natural balance of marine ecosystems. We present the first morphological and ultrastructural evidence of massive acoustic trauma, not compatible with life, in four cephalopod species subjected to low‐frequency controlled‐exposure experiments. Exposure to low‐frequency sounds resulted in permanent and substantial alterations of the sensory hair cells of the statocysts, the structures responsible for the animals' sense of balance and position. These results indicate a need for further environmental regulation of human activities that introduce high‐intensity, low‐frequency sounds in the world's oceans.